Protection of the rights of the child in the Republic of Kazakhstan as an object of state activity: theoretical and practical aspects (Journal of actual problems of jurisprudence, 2023)
The theoretical and practical dimensions of child rights protection in Kazakhstan, emphasizing the nation’s commitment to nurturing the well-being and development of its youngest citizens. Kazakhstan’s legal framework, including its Constitution and international obligations like the United Nations Convention on the Rights of the Child (CRC), underscores the importance of safeguarding children’s rights. A comprehensive legislative framework, comprising laws such as the Law on the Rights of the Child, the Law on Social and Legal Protection of Children Without Parental Care, and the Law on Education, forms the basis for child protection in Kazakhstan. However, the effectiveness of these laws hinges on their consistent implementation and enforcement, which requires strengthening the capacity of institutions and professionals involved in child protection. The article also highlights key child protection institutions and educational awareness programs in Kazakhstan. Nevertheless, persistent challenges, including cultural and traditional barriers, child abuse and neglect, and educational disparities, require holistic approaches for resolution. Bridging educational gaps, especially in rural and marginalized communities, necessitates targeted investments in infrastructure, teacher training, and curriculum development. In conclusion, Kazakhstan’s commitment to child rights protection is evident in its legal framework and international obligations. However, addressing practical challenges requires ongoing evaluation, adaptation, and comprehensive strategies to ensure the full realization of children’s rights. Key words: Kazakhstan, United Nations, law, constitution, rights of the child.